Effects of chitosan combined with nisin treatment on storage quality of large yellow croaker (Pseudosciaena crocea). (15th July 2016) - Hui, Guohua; Liu, Wei; Feng, Hailin; Li, Jian; Gao, Yuanyuan
Highlights: Preservation effects of chitosan with different concentrations of nisin are studied. Volatile spoilage products can be used as the index for croaker fish freshness evaluation. Chitosan with nisin shows better preservation than chitosan. Promotion effect of nisin in low concentration on chitosan is not significant. Chitosan with 0.6% nisin prolongs the shelf life of croakers (>4 days). Abstract: Effects of chitosan combined with different concentrations of nisin on quality enhancement of large yellow croaker ( Pseudosciaena crocea ) stored at 4 °C were evaluated for 8 days. Changes in sensory score and volatile spoilage products, total viable counts (TVC), and physiochemical indexes including weight loss, colour, pH, total volatile basic nitrogen (TVB-N), and K -value were examined. Results demonstrated that nisin-treated samples presented better quality preservation effects than chitosan alone. 1% chitosan combined with 0.6% nisin presented optimal quality enhancement effects, such as moisture loss control, volatile spoilage inhibition, TVB-N reduction, TVC growth control, and colour and sensory acceptability maintenance. Therefore, chitosan combined with nisin is promising in large yellow croaker shelf life extension.